„Zdecydowanie żydowskie, wyraźnie polskie”… Strategie narracyjne twórców Muzeum Historii Żydów Polskich Polin - Cukras-Stelągowska, Joanna (Kultura-Społeczeństwo-Edukacja, 2019)
This paper aims to establish a framework of discursive narratives about the idea of the Polin Museum of the History of Polish Jews. Most of these narrative strategies concern the implementation of this huge project, arrangement of exhibitions, topics presented and the importance of the museum for the community of Polish Jews and Poles. The qualitative analysis of the narratives is conducted based on the content of periodicals published by the Jewish community in Poland: „Midrasz. Pismo Żydowskie” and „Chidusz. Magazyn Żydowski”. The analysis involves 11 speeches given immediately after the ceremonial opening of the Museum in 2013 and later, primarily at anniversary celebrations.